개별환경제어시스템(PECS)을 이용한 국부 온열환경 개선에 관한 연구 - 김이경(Yi-Kyung Kim); 류소임(So-Im Ryu); 김철(Chul Kim) (KIEAE Journal, 2024)
Purpose: In building, the thermal imbalance of radiant heat, and uneven heat distribution of HVAC system impairs the indoor thermal comfort. These issues have more significant physiological impact on the human conditions during the winter. This study aims to analyze the impact of using three Personalized Environmental Control System (PECS) on occupant thermal perception to improve indoor local thermal environment. Method: Two classrooms in P University in Busan were selected to experiment with two different set-point temperatures (i.e., 18℃, 22℃) to reflect actual operating conditions for energy conservation in winter. Local heating to occupants was performed using three types of PECS (i.e., Neck band, Desk fan, and Foot heater). Thermal environment perception survey was conducted to participants to evaluate the impact of each PECS device on thermal metrics (i.e., TSV, TCV, OTA). Result: TSV values with PECS showed the improvement of 27.8% at 18℃ and 48.9% at 22℃ compared to the baseline without PECS. At both indoor set-point temperatures (i.e., 18℃, 2 2℃), the desk fan and foot heater showed a higher improvement effect than the neck band. The use of PECS contributed to improving the overall thermal satisfaction of participants, which varied in effectiveness depending on the application area and capacity of PECS on the body. The findings of this study verified the effectiveness of PECS heating on the improvement of occupants thermal perception in winter. KCI Citation Count: 0